The gargantuan polity : on the individual and the community in the French Renaissance - Randall, Michael, 1953- (University of Toronto Press, 2008)
The Gargantuan Polity examines political, legal, theological, and literary texts in the late Middle Ages, to show how individuals were defined by contracts of mutual obligation, which allowed rulers to hold power due to approval of their subjects.